Multifarious pretreatment strategies for the lignocellulosic substrates for the generation of renewable and sustainable biofuels: A review. (November 2020) - Anu; Kumar, Anil; Rapoport, Alexander; Kunze, Gotthard; Kumar, Sanjeev; Singh, Davender; Singh, Bijender
Abstract: Currently major part of the world's energy requirements is fulfilled by fossil resources. Severe economic and environmental problems along with their limited resources are still a major issue. Long-term environmental and commercial concern has focussed into huge research in the past decades to replace fossil fuels with renewable sources of energy. The main focus of energy research is lignocellulosic substrates, which seems to be the best for energy application due to easily availability, cost-effective and environment favourable production process. Therefore, lignocellulosic materials provide economical, environmental and energetic benefits with an alternative to traditional or high cost substrates. However, the close association of major constituents of lignocellulosic biomass forms different barriers, which hinders the enzymatic hydrolysis of cellulose and hemicellulose to different fermentable sugars. To overcome this problem, different pretreatment approaches including physical, chemical, biological and combination of them have been used to improve the enzymatic accessibility or digestibility of lignocellulosic biomass. Various pretreatment methods have specific effect on different lignocellulosic components. Among all the methods, biological methods have performed better with respect to yield, cost and environmental related problems. Pretreated substrates from various pretreatments have been saccharified for the production of sustainable and renewable biofuels like ethanol, butanol, hydrogen, acetoin and 2, 3-butanediol. Highlights: Multifarious pretreatment strategies for the lignocellulosic substrates. Biological pretreatment of lignocellulosic biomass and analysis. Production of renewable and sustainable biofuels from lignocellulosic substrates. Techno-economical analysis of various pretreatment methods.